Interface Engineering of Metal‐Oxide Field‐Effect Transistors for Low‐Drift pH Sensing (Adv. Mater. Interfaces 20/2021). Issue 20 (22nd October 2021) - Ren, Huihui; Liang, Kun; Li, Dingwei; Zhao, Momo; Li, Fanfan; Wang, Hong; Miao, Xiaohe; Zhou, Taofei; Wen, Liaoyong; Lu, Qiyang; Zhu, Bowen
Abstract : Metal‐Oxide Field‐Effect Transistors In article number 2100314, Huihui Ren, Bowen Zhu, and co‐workers demonstrate that a thin Al2 O3 layer can effectively passivate solution‐processed In2 O3 based field‐effect transistors (FETs), enabling high stability, low leakage current, and low signal drift toward pH sensing. This study opens new opportunities for constructing high‐performance FETs‐based biosensors.